Çocuk Diş Hekimliğinde Ebeveyn Ağız-Diş Sağlığı Okuryazarlığı ve Çocukların Ağız-Diş Sağlığı Üzerindeki Etkileri: EBEVEYN AĞIZ-DİŞ SAĞLIĞI (Turkey Health Literacy Journal, 2025)
Oral health literacy,a relatively new field within the concept of health literacy,refers to individuals’ ability to acquire,process,and apply information related to oral health.Oral health significantly impact not only adults but also children’s health.Children’s oral health is a fundamental aspect of their general well-being,influencing their quality of life in the long run.Oral health problems during childhood can lead to more severe health issues in adulthood.Parents’ level of knowledge about oral health is a crucial factor in shaping children’s dental care habits and preventing oral health problems.This review aims to examine the importance of the relationship between parental oral health literacy and children’s oral health in the context of pediatric dentistry.Researchs indicates that children of parents with low oral health literacy levels are more likely to experience dental caries and periodontal diseases.Parents’ knowledge of oral health directly affects their children’s toothbrushing habits,frequency of dental visits, and overall oral hygiene.Additionally,socioeconomic status,education level,and cultural factors are known to influence parental oral health literacy levels.This review provides recommendations for improving parental oral health literacy.Strategies such as educational programs,increased access to healthcare services,awareness campaigns, and the integration of oral health education into child health programs are considered essential for enhancing children’s long-term oral health. In conclusion, improving parental oral health literacy is highlighted as a critical factor in positively impacting children’s oral health,overall well-being,and quality of life.